Life long follow up and management strategies of patients living with native livers after Kasai portoenterostomy - Patrick Ho Yu Chung (Nature Portfolio, 2021)
Abstract We present a 37 years’ experience in the management of biliary atresia (BA) and discuss long-term complications after Kasai portoenterostomy (KPE). A retrospective territory-wide study from 1980 to 2017 on 231 patients with open KPE from three tertiary paediatric surgical centres was performed. Outcome parameters were clearance of jaundice (COJ), native liver survival (NLS) and long-term complications. Factors affecting the operative outcomes were analyzed. The median duration of follow up was 17.5 (IQR: 13.5–22) years. Over 66% of patients became jaundice-freed at 1 year after KPE. Seventy patients (30.3%) received liver transplant (LT) at a median age of 6.2 (IQR: 4.3–8.4) years. The NLS rates at 10 and 20 years were 70.7% and 61.5% respectively with no significant change over the study period. The median age at KPE was 59 (IQR: 49–67) days. KPE performed before 70 days was associated with higher odd ratios for successful drainage but the age of KPE did not have an impact on the long-term NLS. Among all native liver survivors (n = 153), the median bilirubin level was 24 (IQR: 16–36) µmol/L. Portal hypertension (PHT) and recurrent cholangitis were found in 51.6% and 27.5% of them respectively. With a vigilant follow up program, more than 60% of BA patients could remain stable with the disease and achieve long-term survival without LT. Although cholestasis, portal hypertension and recurrent cholangitis are common in long-term NLS, with a comprehensive follow management strategy, they do not always necessitate LT. Our study serves as an example for countries where deceased donor organs are scarce due to very low donation rate.